2009
DOI: 10.1007/s00380-008-1125-y
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of T-calcium channel blocker treatment on deterioration of renal function in chronic kidney disease

Abstract: Some calcium channel blockers (CCBs) have renoprotective effects. Our aim was to compare the effects of different subclasses of CCBs on the deterioration of renal function in chronic kidney disease (CKD). This is a prospective, observational cohort study in a single center. The subjects were 107 nondiabetic CKD patients. The rate of deterioration of estimated glomerular filtration rate (DeltaeGFR) was calculated by [last visit eGFR - baseline eGFR/follow-up duration]. Multivariate analysis was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…33,34 Our present observations therefore imply a distinct therapeutic applicability of Ca channel blockers in CKD. 31,35 Of note, the present study showed that in patients with proteinuria at baseline, eGFR was lower than in non-proteinuric patients throughout the study period (Figures 4a and b, bottom). These observations are compatible with previous reports showing that proteinuria per se constitutes a risk factor for the development of CKD.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…33,34 Our present observations therefore imply a distinct therapeutic applicability of Ca channel blockers in CKD. 31,35 Of note, the present study showed that in patients with proteinuria at baseline, eGFR was lower than in non-proteinuric patients throughout the study period (Figures 4a and b, bottom). These observations are compatible with previous reports showing that proteinuria per se constitutes a risk factor for the development of CKD.…”
Section: Discussionmentioning
confidence: 52%
“…16 By contrast, novel types of Ca channel blockers, including efonidipine and benidipine, which possess T-type Ca channel blocking activity, 27,28 confer a greater benefit on renal function. 23,[29][30][31] Of interest, efonidipine possesses renal protective action via efferent arteriolar dilation, [17][18][19][20] the inhibition of Rho kinase 32 and, possibly, the inhibition of aldosterone activity. 33,34 Our present observations therefore imply a distinct therapeutic applicability of Ca channel blockers in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…19,20) In fact, it has been reported that T/L-type CCBs dilate both renal afferent and efferent arterioles to decrease intraglomerular pressure in patients with nephritis or nephrosclerosis, 21) with better renal outcomes than those observed for L-type CCBs. 22) The present study compared the L-type CCB amlodipine and T/L-type CCB benidipine in CKD patients with albuminuria. In the amlodipine and benidipine groups in the overall study population, there was no significant improvement in UAE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a prospective cohort study attempting a direct comparison of renal effects of T-type and L-type CCBs in non-diabetic CKD patients reveals more beneficial effects of T-type CCBs than L-type CCBs on renal endpoints [26]. …”
Section: Clinical Studies Using Various Ccbsmentioning
confidence: 99%